2011
DOI: 10.1021/nn102232u
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Structural, Electronic, and Optical Properties of Oxide-Sheathed Silicon Nanowires

Abstract: Using a density functional theory approach, we examine the dielectric function (ε(ω)) optical spectra and electronic structure of various silicon nanowire (SiNW) orientations (<100>, <110>, <111>, and <112>) with amorphous oxide sheaths (-a-SiOx) and compare the results against H-terminated reference SiNWs. We extend the same methods to investigate the effects of surface passivation on <111> SiNW properties using functional group termination (-H, -OH, and -F) and three different thicknesses of oxide sheath pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
(125 reference statements)
1
24
0
Order By: Relevance
“…) of the refractive index are calculated from the real (ε 1 ) and imaginary (ε 2 ) parts of ε m , [32] the Seraphin-Bottka coefficients α and β can be obtained from the relations [33,34]:…”
Section: Theoretical Model Of Strained Gementioning
confidence: 99%
See 1 more Smart Citation
“…) of the refractive index are calculated from the real (ε 1 ) and imaginary (ε 2 ) parts of ε m , [32] the Seraphin-Bottka coefficients α and β can be obtained from the relations [33,34]:…”
Section: Theoretical Model Of Strained Gementioning
confidence: 99%
“…In previous works, these relations between the SeraphinBottka coefficients and ε m have been used by Sundari and Raghavan [34] to evaluate the degree of disorder present in experimental samples of tetrahedrally bonded semiconductors, and by Bondi et al [33] to assess the contribution to optical spectra of suboxide composition and bonding disorder in oxide terminated Si nanowires. In this work, they provide a convenient way to extract parameters for experimental photoreflectance spectra, starting only from plane-wave pseudopotential DFT calculations.…”
Section: Theoretical Model Of Strained Gementioning
confidence: 99%
“…8 Zhao and co-workers studied anhydrous silica sheets and related tubes using first-principles calculations, 21 whereas De Leeuw and co-workers investigated hydration effects on anhydrous silica tubes. [24][25][26][27] To the best of our knowledge, to date theoretical studies on 2D hydrous silica sheets have not yet been reported. [24][25][26][27] To the best of our knowledge, to date theoretical studies on 2D hydrous silica sheets have not yet been reported.…”
Section: Solutions Etc)mentioning
confidence: 99%
“…Furthermore, the identity of the halogen atom was found to impact the resulting bandgap of the system where larger halogen atoms resulted in more pronounced effect on the bandgap. Bondi et al 53 have shown that for SiNWs grown along the [111] orientation, fluorine surface decoration results in increased band density. Studying the effects of crystallographic orientation, Ng et al 61 were found to strongly decrease with respect to the fully hydrogenated counterparts.0 F ⊥ Going beyond SiNW structures, we have recently presented a computational study exploring the structural and electronic properties of fully hydrogenated sp 3 -type silicon nanotubes (SiNTs) grown along various crystallographic directions.…”
Section: U Introductionmentioning
confidence: 99%